The Spiritual and Social Functions of Yasin Verses on the Night of Nisfu Sha‘ban: A Living Qur’an Analysis at the Jami‘ Al-Muttaqien Mosque, South Jakarta: Fungsi Spiritual dan Sosial Surah Yasin pada Malam Nishfu Sya’ban: Analisis Living Qur’an di Masjid Jami Al-Muttaqien Jakarta Selatan - Izza Faizah Khaizarony; Kholilurrahman Kholilurrahman; Nurbaiti Nurbaiti; Eka Kurnia Firmansyah (Institut Agama Islam Negeri Kerinci, 2025)
This study analyzes the spiritual and social functions of the practice of reading Surah Yasin on the night of Nishfu Sha'ban at the Al-Muttaqien Mosque in South Jakarta through the Living Qur'an approach and the perspective of the sociology of religion. This study aims to reveal the ritual structure, the meaning given by the congregation, the social functions, and the dynamics of religious legitimacy that accompany the continuity of this tradition. The findings indicate that the Yasinan ritual has been institutionalized. Thus, this study expands the Living Qur'an study by showing that the Qur'an in the context of the Nishfu Sha'ban ritual functions as a ritual social structure that organizes collective actions, frames the religious experiences of the congregation, and maintains the continuity of religious traditions through established social mechanisms as an annual collective practice passed down from generation to generation, with a relatively stable implementation structure from year to year. The congregation’s interpretation of Surah Yasin is rooted in beliefs regarding its virtues and strengthened by recurring spiritual experiences that foster tranquility and a sense of closeness to God. Moreover, the ritual plays a significant role in strengthening social cohesion, enhancing communal solidarity, and transmitting religious values to younger generations. Despite differing scholarly views on the authenticity of hadiths related to Nishfu Sha’ban, the community responds pragmatically by emphasizing the ritual’s social benefits and spiritual value. This study demonstrates that Yasinan is not merely a spiritual practice but also an adaptive social institution within urban Muslim society. The research opens pathways for further studies in other Muslim communities to better understand contemporary religious practices.